2010
DOI: 10.1016/j.polymdegradstab.2010.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterisation of degrading polycaprolactone scaffolds

Abstract: a b s t r a c tA degradation study investigating the hydrolysis of different scaffolds of polycaprolactone suspended in phosphate buffer solution at 37 C was performed over a three month period. Structures included electrospun fibres, held as 2D mats and 3D bundles, and solvent cast films. These structures and their surrounding solutions were physiochemically characterised using a range of techniques. Changes in scaffold physicochemical properties were observed over the course of the study, including significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
99
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(112 citation statements)
references
References 25 publications
11
99
0
2
Order By: Relevance
“…CIP and PCL are both hydrophobic in nature and could interact among PCL chains chemically, as previously described. 44 Therefore, this could be the reason why the percentages of drug release observed in the present study did not reach 100%, as CIP (hydrophobic drug) was trapped in a PCL (hydrophobic polymer) matrix that did not degrade over 19 days in the present study.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…CIP and PCL are both hydrophobic in nature and could interact among PCL chains chemically, as previously described. 44 Therefore, this could be the reason why the percentages of drug release observed in the present study did not reach 100%, as CIP (hydrophobic drug) was trapped in a PCL (hydrophobic polymer) matrix that did not degrade over 19 days in the present study.…”
mentioning
confidence: 58%
“…43 Bosworth and Downes studied in vitro degradation behavior of the PCL fibers in PBS at 37°C at pH 7.4. 44 Their findings from high-performance liquid chromatography analysis revealed that PCL became more hydrophobic and, hence, is more likely to comprise longer length chains. A slight increase in the degradation by-products (no significant difference over 90 days) was detected, however, and may have been accelerated by autocatalysis occurring secondary to the accumulation of acidic breakdown products.…”
mentioning
confidence: 99%
“…Young's modulus of PCL film increased gradually during incubation, while all composite films showed reduction in E t . Increase in stiffness of PCL film can be attributed to an increase in degree of crystallinity [30,31]. In the case of A2-PCL composites, the biggest changes in E t were noted in the first 3 months, and then, the values stayed on similar level until the end of the test.…”
Section: In Vitro Degradationmentioning
confidence: 94%
“…The hydrolysis of polymer chains increases possibility of recrystallization by reducing their length and increasing mobility. Furthermore, because of low glass transition temperature of PCL (-60°C) mobility of non-degraded chains at 37°C during incubation in aqueous media could be enhanced and solvent-induced crystallization might have occurred [8,[28][29][30]. Although the crystallinity of PCL film increased, the mass loss was not observed, indicating bulk degradation kinetics.…”
Section: In Vitro Degradationmentioning
confidence: 99%
“…Enzymatic degradation studies [26,27] show that erosion occurs at the material surface without depending on hydrophilicity. This is consistent with the fact that hydrophilicity does not change with degradation (Fig 1b).…”
Section: Weight Loss and Swollen Degreementioning
confidence: 99%